Input-output and national accounts - Stone, Richard (Paris : Organisation for European Economic Co-operation, 1961)
This present report carries the examination of conceptual problems one stage further. It deals with the sub-division of the national accounts on a industry basis so as to provide a detailed picture of industrial structure.
Bibliography: p. 191-202.
osa;20/09/18
Loans
Keywords: Industrial management